The role of the RNA binding protein HnRNP K in the pathogenesis of frontotemporal lobar degeneration. (1st February 2022) - Gatt, Ariana; Bampton, Alexander; Humphrey, Jack; Cappelli, Sara; Buratti, Emanuele; Fratta, Pietro; Lashley, Tammaryn
Abstract: Background: HnRNP K is an RNA‐binding protein belonging to the family of heterogeneous nuclear ribonucleoproteins (hnRNPs). Like other hnRNPs such as the better known TDP‐43, hnRNP K is predominantly nuclear where it plays an important role in pre‐mRNA splicing. HnRNPs can also shuttle to the cytoplasm and we find that hnRNP K is predominantly cytoplasmic in pyramidal neurons in Frontotemporal Lobar Degeneration (FTLD). The loss of nuclear hnRNPs in disease states is directly linked to splicing misregulation and aberrant RNA processing. Indeed, loss of nuclear TDP‐43 leads to cryptic exon inclusion in gene targets and the generation of truncated proteins. We aimed to investigate changes in RNA processing and presence of cryptic events upon hnRNP K mislocalisation in FTLD. Method: Bioinformatic analysis of a neuronal cell line with hnRNP K knockdown identified a set of cryptic events. We have validated these events using PCR amplification and gel electrophoresis in both SH‐SY5Y cells with hnRNP K knockdown and in post‐mortem human brain tissue. Result: The loss of nuclear hnRNP K results in the inclusion of cryptic exons in multiple gene targets in both SH‐SHY5Y cells with hnRNP K knockdown and FTLD brain regions exhibiting hnRNP K nuclear loss. Conclusion: The mislocalisation of hnRNP K from the nucleus to the cytoplasm in FTLD is associated with the inclusion of cryptic exons in multiple gene targets. This suggests that similarly to TDP‐43, hnRNP K plays a crucial role in RNA processing and splicing regulation which when impaired could lead to transcriptional dysregulation and disease pathogenesis.